Theoretical investigations of NiTiSn and CoVSn compounds - Mustapha, Hichour; Djamel, Rached; R., Khenata; M. Zouaoui, Rabah; M., Merabet; Ali Hussain, Reshak, Prof. Dr.; S., Omran; Rashid, Ahmed (Elsevier Ltd., 2013)
Link to publisher's homepage at http://www.elsevier.com/